PENENTUAN STRATEGI UNTUK MENINGKATKAN KINERJA KARYAWAN DI BNI KANTOR CABANG SEMARANG DENGAN MENGGUNAKAN METODE AHP (ANALYTICAL HIERARCY PROCESS) - Muchammad Miftahuddin; Antoni Yohanes (Jurnal Ilmiah Dinamika Teknik, 2017)
A company can not be separated from human resources (HR) that work in it. Humans have different levels of individual ability. The company can measure employee performance based on their performance. To be able to improve the performance of every employee the company continues to seek and determine the right strategy to improve the performance of each employee in the PT. BNI Branch of Semarang.Analytical Hierarchy Process (AHP) is a method of decision making on the problem of determining the priority of choice from various strategic alternatives. The determination of alternative strategies is based on criteria such as business ability, management capability and work ability. Based on the above criteria, the determination of stratrgi alternatives is improving the quality of human resources, improving the welfare and improving the work facilities. With AHP method in determining employee performance improvement strategy, the highest priority is the improvement of work facility with priority value of 0.437633649, then the second alternative is the improvement of the quality of human resources with the priority value of 0.358082139, and the last alternative is the improvement of welfare with the priority value of 0.254133181.Keywords: Employee Performance, AHP